2006
DOI: 10.1136/gut.2005.078824
|View full text |Cite
|
Sign up to set email alerts
|

Gut-associated bacterial microbiota in paediatric patients with inflammatory bowel disease

Abstract: Background: Clinical and experimental observations in animal models indicate that intestinal commensal bacteria are involved in the initiation and amplification of inflammatory bowel disease (IBD). No paediatric reports are available on intestinal endogenous microflora in IBD. Aims: To investigate and characterise the predominant composition of the mucosa-associated intestinal microflora in colonoscopic biopsy specimens of paediatric patients with newly diagnosed IBD. Methods: Mucosa-associated bacteria were q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
227
3
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(250 citation statements)
references
References 48 publications
11
227
3
9
Order By: Relevance
“…Furthermore, the organisms least likely to be aff ected would be those with adherent properties, of most interest in the mucosal disease of IBD. In support of our approach, other investigators have demonstrated diff erences in the IBD microbiota despite prior bowel preparation ( 10,29 ). Finally, a study design where children undergo diagnostic colonoscopy under general anesthetic without adequate preparation would be ethically unacceptable.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the organisms least likely to be aff ected would be those with adherent properties, of most interest in the mucosal disease of IBD. In support of our approach, other investigators have demonstrated diff erences in the IBD microbiota despite prior bowel preparation ( 10,29 ). Finally, a study design where children undergo diagnostic colonoscopy under general anesthetic without adequate preparation would be ethically unacceptable.…”
Section: Discussionmentioning
confidence: 56%
“…Most E. coli strains isolated from the ileal mucosa of CD patients are able to adhere to and invade intestinal epithelial cells (14)(15)(16) and belong to the pathogenic group of adherent invasive E. coli (AIEC) (17). AIEC is highly associated with the ileal mucosa in CD patients (14)(15)(16)(18)(19)(20)(21)(22)(23). CD-associated AIEC cells adhere to the brush border of primary ileal enterocytes isolated from CD patients but not to enterocytes isolated from controls without inflammatory bowel disease.…”
mentioning
confidence: 99%
“…12,13 At least 1 category of JIA has been associated with distinct intestinal microbial populations. 14 Antibiotics can alter some subjects' intestinal microbiota for $6 months.…”
Section: What's Known On This Subjectmentioning
confidence: 99%